2011
DOI: 10.1590/s0103-84782011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Rizóbios nativos do Rio Grande do Sul simbioticamente eficientes em Lotus glaber

Abstract: As leguminosas forrageiras, além de contribuírem para o aumento da oferta de forragem com alto teor de proteína, também são importantes como cobertura vegetal de solos. Entre as leguminosas com grande potencial forrageiro, espécies do gênero Lotus têm se destacado. Este trabalho visou à seleção de rizóbios nativos eficientes em Lotus glaber a partir de amostras de solo de cinco localidades do Rio Grande do Sul. Obtiveram-se 259 isolados de rizóbios, que foram avaliados quanto à morfologia colonial e produção d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The isolates UFRPE Cm244 and 677 were generally effective, and their average SNA was around 83 and 85 % of that accumulated by plants receiving 120 kg ha -1 N. These effects are similar to those found by Fontoura et al (2011) who found that inoculated Lotus glaber plants, cultivated in Leonard jars, accumulated similar levels of N as plants fertilized with 100 kg ha -1 N.…”
Section: Resultssupporting
confidence: 85%
“…The isolates UFRPE Cm244 and 677 were generally effective, and their average SNA was around 83 and 85 % of that accumulated by plants receiving 120 kg ha -1 N. These effects are similar to those found by Fontoura et al (2011) who found that inoculated Lotus glaber plants, cultivated in Leonard jars, accumulated similar levels of N as plants fertilized with 100 kg ha -1 N.…”
Section: Resultssupporting
confidence: 85%
“…These results demonstrate the high efficiency of these isolated (Table 3) which were higher than those found in the literature, as the study of symbiosis between rhizobia grown forage legumes (Scheffer-Basso et al, 2001;Frizzo, 2007) and (Scheffer-Basso et al, 2001). Fontoura et al (2011) obtained similar results with the inoculation of rhizobia in Lotus glaber.…”
Section: Discussionsupporting
confidence: 65%
“…Deficiencies in N and P are generally the main reason for pasture degradation (Boddey et al, 2004), particularly N deficiency caused by high N losses from soil-plant-animal systems (Lira et al, 2006). An interesting alternative that could retain N in pasture soils are legume-grass consortiums, in view of their ability to fix atmospheric N 2 (Santos et al, 2005;Fontoura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%